Federal Policy for Financially-Distressed Subnational Governments: The U.S. States and Puerto Rico - Cheryl D. Block (Washington University Journal of Law & Policy, 2017)
This Article addresses the aftermath of the Great Recession specifically focusing on its effects at the local and statewide levels. Block uses the financial situation in Puerto Rico to detail the common presumption against the use of federal government assistance to financially-distressed subnational governments. Block then analyzes rebuttal arguments that the states and Puerto Rico might use to overcome the initial presumption against federal assistance and gives suggestions to facilitate the structuring of relief efforts in the rare circumstances when federal intervention is warranted.
Keywords: subnational government bailout; fiscal austerity; public debt; Puerto Rico; Great Recession; subnational governments; federal assistance; federal intervention; Puerto Rico Oversight; Management; and Economic Stability Act; PROMESA